(untitled) (Bulletin of Pure and Applied Sciences-Chemistry, 2022)
Silicon is the most obvious potential substitute for carbon, and the Possibility of Silicon-Based Life is the focus of the work. An analysis of the sites of action of four silicon-based exobiological nanomolecules, determined by the distribution of electrical charges around the nanomolecules atoms called: ASi, CSi, GSi and TSi. The Van der Waals radius distribution calculations have been determined via ab initio Hartree-Fock methods, Unrestricted and Restrict (UHF and RHF) in the set of bases used Effective Core Potential (ECP) minimal basis, and CC-pVTZ (Correlation consistent valence-only basis sets triple-zeta). Polymers can also be assembled as chains of alternating elements such as Si-C, Si-O, and B-N. Alternation with carbon is used to some extent in terran organisms (such as C-C-N in proteins and C-C-C-O-P-O in nucleic acids), and silated compounds play important structural roles in the cells of many organisms on Earth.